Initial growth of coffee tree with use of hidro retentor polymer and different intervals of watering - Conte e Castro, Ana Maria; Maia, Guilherme Martins; de Souza, Juliana Aparecida; Alves Manfio, Frederico Luiz (Coffee Science - ISSN 1984-3909, 2014)
With the objective to evaluate the effect of hidro retentor polymer and different watering intervals on the initial growth of shoot and roots of the coffee tree, an experiment was conducted in pots, in the Universidade Estadual do Norte do Paraná, Campus Luiz Meneghel Bandeirantes/PR. The experimental design was a randomized block factorial design 4x3, using four replicater. The treatments consisted of four levels of hidro retentor polymer (0; 0.5; 2 and 4 kg ha-1) and three watering intervals (3, 7, 14 days). Fifty days after transplantation were evaluated: the growth of plant height, stem diameter, number of leaves, fresh and dry weight of shoot and roots and root density. Increased doses of hidro retentor polymer up to 4 kg ha-1 positively influenced the stem diameter of the coffee tree. The use of hidro retentor polymer in the dose of 4 kg ha-1 and watering intervals up to seven days, increases root density of coffee, at fifty days after transplantation.